2017
DOI: 10.1080/09537104.2017.1356452
|View full text |Cite
|
Sign up to set email alerts
|

Platelet aggregation impacts thrombin generation assessed by calibrated automated thrombography

Abstract: A calibrated automated thrombogram (CAT) is performed usually with human platelet-free plasma (PFP) but may be more relevant with platelet-rich plasma (PRP). In this case, platelets are not stimulated by subendothelial molecules like collagen. Our aim was to assess the consequence of strong (collagen) or weak (ADP) induction of platelet release and aggregation on thrombin generation. Platelet aggregation in PRP was triggered with 10 µg/mL collagen or 10 µM ADP using a lumi-aggregometer. Thrombin generation cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…We found that QPD is associated with significant PRP but not PPP TG abnormalities, with strong associations between QPD platelet (but not plasma) FV levels and QPD PRP ETP and peak thrombin concentration. Interestingly, platelet-activating agonists improved PRP TG, as anticipated, 29 without accentuating the QPD PRP TG defect.…”
Section: Discussionsupporting
confidence: 70%
“…We found that QPD is associated with significant PRP but not PPP TG abnormalities, with strong associations between QPD platelet (but not plasma) FV levels and QPD PRP ETP and peak thrombin concentration. Interestingly, platelet-activating agonists improved PRP TG, as anticipated, 29 without accentuating the QPD PRP TG defect.…”
Section: Discussionsupporting
confidence: 70%
“…Platelet aggregation was triggered by 2 µg/mL equine collagen fibrils type I (Chrono-log Corp, Havertown, PA, USA). Aggregated PRP was used directly after aggregation for CAT measurement [14].…”
Section: Methodsmentioning
confidence: 99%
“…In the present work, we aimed to explore the origin and determinants of camel-back shaped TG curves in the presence of new oral anticoagulants, in particular rivaroxaban. We took advantage of the use of aggregated platelet rich plasma (PRP/agPRP) in the CAT [14] which fully includes platelet procoagulant activity since modified TG kinetics in particular faster TG could compensate the slow TG often observed after rivaroxaban treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence and mouse models demonstrate that platelet-cancer cell interaction is crucial for cancer metastasis [ 23 ]. Platelets, originally derived from megakaryocytes in the bone marrow [ 24 ], are the key regulator of thrombosis [ 25 , 26 ]. The major function of platelets is to prevent bleeding and reduce blood loss in case of vascular injury [ 27 ].…”
Section: Introductionmentioning
confidence: 99%